Deletion of Mex3c gene leads to autistic-like behavior in mice by inhibiting AMPK signal pathway - Cai, Hui; Zhang, Chengping; Zhang, Haonan; Du, Yong; Wang, Kai (Frontiers in Behavioral Neuroscience, 2025)
IntroductionAutism Spectrum Disorder (ASD) is a hereditary neurodevelopmental condition influenced by genetic alterations, particularly in genes regulating neural development and synaptic plasticity. Emerging evidence suggests that the Mex3c gene plays a role in energy metabolism and neuronal development, indicating its potential relevance to ASD pathogenesis.MethodsTo investigate the role of Mex3c in ASD, we generated Mex3c knockout (KO) mice and conducted a series of behavioral tests, histological analyses, and molecular assays. Behavioral phenotyping included elevated plus maze, open-field test, and three-chamber social interaction test. Histological assessments included Nissl staining, Golgi-Cox staining, and transmission electron microscopy. Molecular evaluations included Western blotting and analysis of the AMPK/SIRT1/PGC1α signaling pathway.ResultsMex3c KO mice exhibited autistic-like behaviors, including social deficits and anxiety-like traits. These behavioral abnormalities were accompanied by reduced neuronal number, decreased dendritic spine density, and impaired synaptic protein expression in the hippocampus. Mitochondrial structural damage and dysfunction were observed, alongside suppression of the AMPK/SIRT1/PGC1α signaling pathway.ConclusionOur findings suggest that Mex3c gene deletion induces ASD-like phenotypes in mice, potentially through disruption of mitochondrial function and synaptic integrity via the AMPK/SIRT1/PGC1? pathway. These results support the candidacy of Mex3c as a susceptibility gene for ASD and highlight mitochondrial signaling pathways as potential therapeutic targets.